Trends on management education an interview with Mary Jo Hatch - Davel, Eduardo; Paternostro Melo, Vanessa (Organizações & Sociedade, 2017)
During her presence at Federal University of Bahia in March, 2006, for an opening conference on Organization theory, at the NPGA (Post-graduate Centre on Administration), CIAGS (Interdisciplinary Centre of Development and Social Management) linked to the ANPAD´s Program on Teaching Development, Mary Jo Hatch (the C. Coleman McGehee Eminent Scholars Research Professor of Banking and Commerce at McIntire School of Commerce, University of Virginia) provided us, on behalf of the Organizações & Sociedade Journal, with an interview about management education. Mary Jo Hatch has a Ph.D. in Organization Behavior from Stanford University and her research has been published in many international journals on management. She is also past chair of the Organization and Management Theory Division of the Academy of Management and the author of many books, such as: Organization Theory: Modern, Symbolic and Postmodern Perspectives (Oxford University Press), The Expressive Organization: Linking Identity, Reputation and the Corporate Brand (co-edited with M. Schultz and M. H. Larsen) and Organization Identity: A Reader (co-edited with M. Schultz), and The Three Faces of Leadership: Manager, Artist, Priest (with M. Kostera and A. Kozminski).